2021
DOI: 10.1177/13678779211004610
|View full text |Cite
|
Sign up to set email alerts
|

Taking care of business: The routines and rationales of early-career musicians in the Dutch and British music industries

Abstract: This article explores a small sample of musicians in two European musical contexts – the Netherlands and the UK. It examines the relationship between the conditions of national music industries and the strategies used to negotiate a career in music and the extent to which musicians frame their careers as entrepreneurs. Interview data from two projects with early-career musicians form the basis of our secondary comparative analysis. We argue that their strategizing can be framed as a set of responses to their l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
0
9
0
3
Order By: Relevance
“…Musicians' financial income and welfare have always been debatable in many countries. Everts and Haynes (2021) have conducted research on British and Dutch early-career musicians. They find that musicians from both areas are pessimistic about their financial future.…”
Section: Resultsmentioning
confidence: 99%
“…Musicians' financial income and welfare have always been debatable in many countries. Everts and Haynes (2021) have conducted research on British and Dutch early-career musicians. They find that musicians from both areas are pessimistic about their financial future.…”
Section: Resultsmentioning
confidence: 99%
“…His research revealed the profound dilemma between musicians’ traditional view of the art and the necessity to change and adapt their business models depending on the economic conditions. Everts and Haynes ( 2021 ) studied the contexts of the British and Dutch music markets and found that musicians’ entrepreneurial identity is based on the rapid change of musical contexts and local contexts. The Netherlands has been building an institutionalized pathway to let musicians’ artistic needs meet their entrepreneurial sensibility.…”
Section: Content Analysismentioning
confidence: 99%
“…Instead, they talk of the increasing commodification of music where solid experience and career building seem to be an illusion. Therefore, we have to ask why there are always more young people trying to establish a career in music (Everts and Haynes 2021 ).…”
Section: Content Analysismentioning
confidence: 99%
“…First, the position that a worker has, and the structural conditions of that position, affects the opportunities for action. For example, research in music has shown that the strategies of musicians can be understood as a response to the specific configuration of the local industry (Everts & Haynes, 2021;Tarassi, 2018). Furthermore, workers strategize their actions by reflecting on their current and desired position.…”
Section: Building a Career In A Changing Marketmentioning
confidence: 99%